Evocative Words: The Poetic Thinking of Martin Heidegger and Daodejing - Francescato, Sara (Aesthetica Preprint, 2023)
The purpose of this essay is to investigate what kind of connections and similarities can be found between the post-Kehre Heideggerian philosophy and the ideas of the Daodejing. The analysis will focus on how Heidegger’s inclination to the poetic language and his rejection of the language of metaphysics find resonances with the allusive saying and the opposition to the declarative language present in the Daodejing. Furthermore, it will be examined how the Daoist ideas can contribute to Heidegger’s attempt to start a “new beginning” for philosophy, possible only by using a language radically different from the metaphysical one, i.e. the evocative language of poetry. Through the examination of the Heideggerian and Daoist positions, this essay also proposes a further reflection on the relationship between poetry and thinking, and its implications for philosophy.